A novel and selective fluorescent ligand for the study of adenosine A2B receptors - Foteini Patera; Sarah J. Mistry; Nicholas D. Kindon; Eleonora Comeo; Joelle Goulding; Barrie Kellam; Laura E. Kilpatrick; Hester Franks; Stephen J. Hill (Wiley, 2024)
Abstract Fluorescent ligands have proved to be powerful tools in the study of G protein‐coupled receptors in living cells. Here we have characterized a new fluorescent ligand PSB603‐BY630 that has high selectivity for the human adenosine A2B receptor (A2BR). The A2BR appears to play an important role in regulating immune responses in the tumor microenvironment. Here we have used PSB603‐BY630 to monitor specific binding to A2BRs in M1‐ and M2‐like macrophages derived from CD14+ human monocytes. PSB603‐BY630 bound with high affinity (18.3 nM) to nanoluciferase‐tagged A2BRs stably expressed in HEK293G cells. The ligand exhibited very high selectivity for the A2BR with negligible specific‐binding detected at NLuc‐A2AR, NLuc‐A1R, or NLuc‐A3R receptors at concentrations up to 500 nM. Competition binding studies showed the expected pharmacology at A2BR with the A2BR‐selective ligands PSB603 and MRS‐1706 demonstrating potent inhibition of the specific binding of 50 nM PSB603‐BY630 to A2BR. Functional studies in HEK293G cells using Glosensor to monitor Gs‐coupled cyclic AMP responses indicated that PSB603‐BY630 acted as a negative allosteric regular of the agonist responses to BAY 60-6583. Furthermore, flow cytometry analysis confirmed that PSB603‐BY630 could be used to selectively label endogenous A2BRs expressed on human macrophages. This ligand should be an important addition to the library of fluorescent ligands which are selective for the different adenosine receptor subtypes, and will enable study of the role of A2BRs on immune cells in the tumor microenvironment.